Estimating the human health risks from polychlorinated dioxins and furans in stack gas emissions from combustion units: implications of USEPA's dioxin reassessment - Bell, John U. (Waste management (Elmsford), 2002)
Shortly after promulgation of the Hazardous Waste Combustor MACT rule established regulatory limits for polychlorinated dioxins and furans (dioxins/furans) in incinerator stack gas, the US Environmental Protection Agency (USEPA) announced that facilities could still be required to demonstrate that stack emissions do not present an unacceptable risk to human health and the environment. Guidance for conducting this risk assessment activity, which was to be required under RCRA omnibus authority, was developed by the agency and released in 1998. The guidance represented an increase in complexity over previous documents developed by the agency and contains multiple chemical, fate and transport, and toxicological parameters which are to be used as default deterministic parameters in a complex series of algorithms which ultimately lead to numerical estimates of risk. As these changes were occurring, USEPA was also moving towards completion of its reassessment of dioxin. That series of documents has been the subject of considerable controversy and has, in several of its various drafts, proposed a number of changes, including modification of the existing toxic equivalency factor (TEF) approach and of the cancer potency factor of 2,3,7,8-tetachlorodibenzo- p-dioxin. At this time it is unclear what the impact of these changes will be on facilities progressing through the permitting process, because it is not intuitively obvious how changes in the risk assessment input parameters will impact the magnitude of the dioxinlfuran risk. In this paper, the receptor usually associated with the highest potential risk from dioxins/furans in a combustion risk assessment, the Subsistence Farmer, will be subjected to a sensitivity analysis to determine which of the multiple default input parameters will have the greatest influence on the potential cancer risk.